Application Of E-Government In Welcoming The Era Of Contemporary Industrial Revolution 4.0 In Indonesia - P. Jefri Leo Chandra S; Adriana Grahani Firdausy (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
This research aims to find out and examine the application of e-government in welcoming the era of the industrial revolution 4.0 which has recently been very influential in aspects of life in Indonesia. This is very interesting to study because during this transition period all countries and especially Indonesia have implemented the role of industry 4.0 in government components. The research method used in this research uses a type of normative legal research, with the research approaches used being a statutory approach and a case approach. The results of the first research analysis show that the development of the e-government system in Indonesia has begun to increase in quantity, but in terms of quality it is still inadequate because the implementation of e-government has not been evenly distributed throughout the region and it still only functions as a provider of static information. Second, there are fundamental obstacles in the implementation of e-government. -government in the industrial revolution 4.0 is at the regional government level, including; the initiative and meaning of e-government implementation by autonomous regional governments is still individual; implementation via the regional website is not yet supported by an effective management system and work processes due to the readiness of regulations, procedures and limited human resources; Many local governments identify the implementation of e-government as simply creating a local government website (web presence). Third, the projection of e-government in the future, whether the industrial revolution 4.0 is still ongoing or in the future after undergoing regeneration, must have the best formulation, including: ( 1) Good legal regulatory order and legal protection. (2) The government is proclaiming education, especially in the IT sector, as the formation of qualified human resources from now on. (3) Adequate infrastructure and availability of access media. (4) Formation of good character and work ethic for human resources for government officials. (5) Changing the mindset of the apparatus to become a disruptive mindset of the apparatus in Indonesia. (6) The industrial revolution 4.0 is based on a mental revolution. (7) Creating reliable Intrepreneurial Leadership. (8) Strengthening religious education.